Junior would mark encyclopedia of world holidays - Griffin, Robert H.; Shurgin, Ann H. (U·X·L, 2000)
Alphabetically arranged entries provide descriptions of celebrations around the world of some thirty holidays and festivals, including national and cultural holidays, such as Independence day and New Year's Day, which are commemorated on different days for different reasons in a number of countries.